Encyclopedia of pasta - Zanini De Vita, Oretta, 1936- (California studies in food and culture ;, 2009)
Spaghetti, gnocchi, tagliatellea, ravioli, vincisgrassi, strascinati--pasta in its myriad forms has been a staple of the Mediterranean diet longer than bread. This beautiful volume is the first book to provide a complete history of pasta in Italy, telling its long story via the extravagant variety of shapes it takes and the even greater abundance of names by which it is known. Food scholar Oretta Zanini De Vita traveled to every corner of her native Italy, recording oral histories, delving into long-forgotten family cookbooks, and searching obscure archives to produce this rich and uniquely personal compendium of historical and geographical information. For each entry she includes the primary ingredients, preparation techniques, variant names for the same pasta, and the locality where it is made and eaten. Along the way, Zanini De Vita debunks such culinary myths as Marco Polo's supposed role in pasta's story even as she serves up a feast of new information. Encyclopedia of Pasta, illustrated throughout with original drawings by Luciana Marini, will be the standard reference on one of the world's favorite foods for many years to come, engaging and delighting both general readers and food professionals.